Predictors of burnout among HIV nurses in the Western Cape - Rizwana Roomaney; Jeanette Steenkamp; Ashraf Kagee (Curationis, 2017)
Background: Burnout has been implicated as one of the reasons for key healthcare personnel, such as nurses, leaving their profession, resulting in insufficient staff to attend to patients. Objective: We investigated the predictors of three dimensions of burnout, namely emotional exhaustion, depersonalisation and personal accomplishment, among nurses in South Africa attending to patients living with HIV. Method: Participants were recruited at a large tertiary hospital in the Western Cape region, with the help of the assistant director of nursing at the hospital. They completed the Maslach Burnout Inventory, the Quantitative Workload Inventory, the Interpersonal Conflict at Work Scale, the Organisational Constraints Scale, the Death and Dying subscale of the Nursing Stress Scale, and the HIV and AIDS Stigma Instrument – Nurse. Results: We found elevated levels of burnout among the sample. Workload, job status and interpersonal conflict at work significantly explained more than one-third of the variance in emotional exhaustion (R² = 0.39, F(7, 102) = 9.28, p = 0.001). Interpersonal conflict, workload, organisational constraints and HIV stigma significantly explained depersonalisation (R² = 0.33, F(7, 102) = 7.22, p = 0.001). Job status and organisational constraints significantly predicted personal accomplishment (R² = 0.18, F(7, 102) = 3.12, p = 0.001). Conclusion: Factors such as workload, job status and interpersonal conflict in the work context, organisational constraints and stigma associated with HIV were found to be predictors of burnout in the sample of nurses. Our recommendations include developing and testing interventions aimed at reducing burnout among nurses, including reducing workload and creating conditions for less interpersonal conflict at work.